Implementing Personalized Learning in Universities Classrooms: Lecturers’ Challenges and Perceptions - Herawati, Agnes (Bina Nusantara University, 2023)
The research aimed to investigate the challenges faced by university lecturers and how they overcome them, as well as the perceptions towards the implementation of a personalized learning approach. Personalized learning was considered a teaching approach that emphasized how to achieve the learning objectives, students’ active learning, and self-regulated learning that could not be fully served in traditional classes. This approach focused on each student’s learning pace and their active participation in the learning process. In the long run, implementing personalized learning was hoped to develop students into responsible and lifelong learners. Although lecturers showed an excellent perception of the implementation of personalized learning, however, it was no doubt that conducting this approach brought some new experiences and challenges for the lecturers as well. Mixed method was applied in the research. The result shows the difference between personalized learning and traditional one in terms of time management, students’ responsibilities and motivations, and class interaction, and those become the most challenging matters faced by the lecturers. How lecturers make use of technology to realize better-personalized learning classes and other crucial things that are needed by the lecturers in implementing personalized learning are also presented.